KEPEMIMPINAN TRANFORMATIONAL DALAM PELAKSANAAN KEHUMASAN BERBASIS MULTIMEDIA - Mu’awanah, Risalatul; Qoyyimah , Uswatun; Yahya Ashari, M. (ILJ: Islamic Learning Journal, 2024)
Globalization and information technology are things that cannot be avoided in competition between educational institutions. The competitiveness of an institution is an important consideration for maintaining its essence and existence as well as reading opportunities in the realm of education. Almost all educational institutions or schools have 'public relations' in their organizational structure which functions to manage many media as a liaison between the institution and the community. Considering the importance of the public relations function for schools, public relations performance needs to receive attention from school leaders. The leadership needs to apply the right leadership model so that public relations can achieve its vision optimally, one of which is by implementing transformational leadership in the field of multimedia-based public relations. The aim of this research is to analyze the performance of multimedia-based public relations, the transformational leadership model applied in the implementation of public relations and the characteristics of transformational leadership that dominate in the implementation of public relations at SMA DU 2 Unggulan BPPT Jombang. This type of research is field research with a qualitative approach. The results of this research show that the performance of public relations at SMA DU 2 Unggulan BPPT is ideal in accordance with McElreath's theory of public relations implementation which applies the stages of planning, organizing and evaluating, the head of public relations has implemented transformational leadership which has four characteristics, namely idealized influence, inspirational motivation, intellectual stimulation and individualized consideration according to Bass theory. Meanwhile, the dominant characteristics of transformational leadership based on research analysis are idealized influence and individual consideration